2022
DOI: 10.1111/jcpe.13621
|View full text |Cite
|
Sign up to set email alerts
|

CPNE7 regenerates periodontal ligament via TAU‐mediated alignment and cementum attachment protein‐mediated attachment

Abstract: Aim Once the periodontal ligament (PDL) is damaged, it is difficult to regenerate its characteristic structure. Copine7 (CPNE7) reportedly plays a functional role in supporting periodontal attachment and PDL alignment. Here we demonstrate the regulatory mechanism of CPNE7 coordination with cytoskeleton reorganization and cementum attachment protein (CAP)‐mediated attachment in PDL regeneration. Materials and Methods The expression and localization of CPNE7, α‐TUBULIN, ACTIN, and microtubule associated protein … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…CPNE7 is a pre-ameloblast-derived protein that has an important role in inducing odontoblast differentiation (63). Bai et al found that CPNE7 is beneficial to the recovery of damaged periodontal ligament by regulating tubulin-mediated cytoskeleton reorganization (64). HSF4 regulates lens development and prevents cataracts in a zebrafish model by activating p53 and its downstream genes (65).…”
Section: Discussionmentioning
confidence: 99%
“…CPNE7 is a pre-ameloblast-derived protein that has an important role in inducing odontoblast differentiation (63). Bai et al found that CPNE7 is beneficial to the recovery of damaged periodontal ligament by regulating tubulin-mediated cytoskeleton reorganization (64). HSF4 regulates lens development and prevents cataracts in a zebrafish model by activating p53 and its downstream genes (65).…”
Section: Discussionmentioning
confidence: 99%
“…PDLSCs transplanted into a periodontal lesion in a rat model generated typical PDL-like structures in vivo by forming Sharpey’s-fiber-like collagen bundles that are connected to cementum-like structures [ 20 ]. New insights into the molecular regulation of periodontal attachment have been brought by Bai S et al, who investigated the regulatory mechanism of copine 7 (CPNE7) and cementum attachment protein (CAP) in coordination with cytoskeleton arrangement [ 24 ]. Regenerating cementum is regarded as key to promoting new fibrous tissue attachment, preserving the PDL, and avoiding tooth ankylosis [ 25 ].…”
Section: The Role Of Pdl Cellsmentioning
confidence: 99%